'You have to do what is best': The lived reality of having a child who is repeatedly hospitalized because of acute lower respiratory infection - Karen McBride‐Henry; Charissa Miller; Adrian Trenholm; Tara N. Officer (Wiley, 2022)
Abstract Introduction Hospitalization of children is traumatic for children and their families. Little is known about the impact of repeated acute admissions on families, or of these experiences in Indigenous populations and ethnic minorities. This study explores the societal and health experiences for families who have a child under two years of age, admitted to hospitals more than twice for lower respiratory infections. Methods Underpinned by a reflective lifeworld research methodology, this article presents results from 14 in‐depth interviews in Aotearoa/New Zealand. Results Families learn to identify illness early and then navigate hospital systems. These families struggle to create safe spaces for their children at home or in society. Wider social and economic support are central to family resilience, without which they struggle. Conclusion This study reinforces the importance of bringing meaningful, culturally‐responsive care to the fore of treatment, particularly when managing vulnerable minorities. Formal referral and support processes are key to this responsiveness to lessen the burdens of acute admissions for families. Patient or Public Contribution Families chose to be involved in this study to highlight the importance of the topic and their experiences with accessing health care. The cultural advisors to the project provided feedback on the analysis and its applicability for the participant community.